Toxoplasma gondii virulence factor ROP1 reduces parasite susceptibility to murine and human innate immune restriction - Butterworth, Simon; Torelli, Francesca; Lockyer, Eloise J.; Wagener, Jeanette; Song, Ok-Ryul; Broncel, Malgorzata; Russell, Matt R. G.; Moreira-Souza, Aline Cristina A.; Young, Joanna C.; Treeck, Moritz (PLoS pathogens, 2022)
Toxoplasma gondii is an intracellular parasite that can infect many host species and is a cause of significant human morbidity worldwide. T . gondii secretes a diverse array of effector proteins into the host cell which are critical for infection. The vast majority of these secreted proteins have no predicted functional domains and remain uncharacterised. Here, we carried out a pooled CRISPR knockout screen in the T . gondii Prugniaud strain in vivo to identify secreted proteins that contribute to parasite immune evasion in the host. We demonstrate that ROP1, the first-identified rhoptry protein of T . gondii , is essential for virulence and has a previously unrecognised role in parasite resistance to interferon gamma-mediated innate immune restriction. This function is conserved in the highly virulent RH strain of T . gondii and contributes to parasite growth in both murine and human macrophages. While ROP1 affects the morphology of rhoptries, from where the protein is secreted, it does not affect rhoptry secretion. Finally, we show that ROP1 co-immunoprecipitates with the host cell protein C1QBP, an emerging regulator of innate immune signaling. In summary, we identify putative in vivo virulence factors in the T . gondii Prugniaud strain and show that ROP1 is an important and previously overlooked effector protein that counteracts both murine and human innate immunity.